BALAGTAS’ FOURTH REVOLT IN DEAD BALAGTAS - Acuña, Arbeen R. (Journal of English Studies and Comparative Literature; Vol 17 (2018), 2019)
This paper looks into the influence of the poet Francisco Balagtas (1788-1862) on the webcomics Dead Balagtas (2013-present) by Emiliana Kampilan, who acknowledges that her work tries to express the revolts of its namesake. Kampilan is an avatar / character / author created by an anonymous author. In the essay “Apat na Himagsik ni Balagtas” (Four Revolts of Balagtas) (1988), Lope K. Santos enumerated what the poet was revolting against: cruel government, religious conflict, bad attitude, and mediocre literature. This paper focuses on the last revolt to show how Kampilan leads by example of what an imagetext (Mitchell 1994) can be and how the medium operates toward potential “critical comedy” (McGowan 2014). As Balagtas utilized the popular form of awit or corrido to interrogate colonialism and its consequences, Kampilan maximizes contemporary web komix that references various types of texts to critically analyze neocolonialism, neoliberalism and hegemony. She also mocks the privileged status and sense of entitlement of the elite and the middle class—those expected to access, read, and understand her works; thus, the avatar-author, being a petty bourgeois herself, exhibits self-reflexivity and encourages an attitude of being self- and class-critical among her target readers. By combining elements that appeal to consumers of popular entertainment as well as to students and enthusiasts of literature and history, Kampilan proposes a novel way of creating komix, and, in the process, advances a standard that balances complex forms with substantial content.